Parameters Related to Nodulating Ability of Some Legumes - Viliana Vasileva (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2017)
Parameters related to nodulating ability of some legumes were studied in a pot trial in the Institute of Forage Crops, Pleven, Bulgaria during the 2013 and 2014 years. Birds foot trefoil (Lotus corniculatus L.), sainfoin (Onobrychis viciifolia Scop.) and subterranean clover (Trifolium subterraneum L.) were pure cultivated and in mixture with perennial ryegrass (Lolium perenne L.) in the next ratios: birds foot trefoil + perennial rye grass (50:50%); sainfoin + perennial ryegrass (50:50%); subterranean clover + perennial rye grass (50:50%); birds foot trefoil + subterranean clover + perennial rye grass (33:33:33%); sainfoin + subterranean clover + perennial rye grass (33:33:33%). From the pure cultivated crops, birds foot trefoil showed both, the highest nodulating ability and root biomass to nodule number ratio. Birds foot trefoil and subterranean clover in mixtures with perennial rye grass formed more nodules as compared to pure crops by  16.0% and by 24.4%, respectively. Sainfoin showed weak nodulating ability, both, pure and in mixtures. In terms of root to above ground biomass ratio, the legumes were arranged as follows: subterranean clover, birds foot trefoil and sainfoin.